Il Sistema Bancario di Fronte ai Problemi Economici - Bozdo, Anila; Koka, Mimoza (European Journal of Sustainable Development, 2014)
Abstract The deteriorating reasons of banking portfolio loans and some necessary measures for the improvement of this situation will be main topics of this article. The corruption in the banking system, is a phenomenon that has passed unobserved, but for our opinion is very often. Non professional loan officers, who lack the essential knowledge of identifying the clients, are common among the Banks of Albania; The new banking system, appears with the old problems of expansion of loan portfolio during 2005-2007,without the bank capacity to manage them and that for sure will be accompanied with influx of many clients with problems. The objective reason is also economic situation of our country and our region that for sure will reflect in quality of loans portfolio; The measures that are important to take are: a reform in banking system for what it concerned structure management in charge of loans giving. The loan officers reward should be connected with quality of portfolio management. Bank of Albania should enforce banks to spend more for training the loan officer. It may organize itself the training courses by raising a training center. It should control on-site banks more frequently. Should pay attention on giving new loans, which will improve gradually the quality of loan portfolio. Despite the situation must not restraint the loan process in bank. Keywords : Nonperforming loans, loan officer; corruption; financial crisis.